Enhanced Image Processing Techniques Based On Technical Challenges In Mammogram Image Characteristics - Nordin, Zailani Mohd (2010)
Breast cancer is the leading type of cancer in Malaysia. More than 30% of total cancer case reported among women in Malaysia is made up of breast cancer. At the moment, one of the best known techniques used for breast cancer detection is mammography. Unfortunately, the image produced through mammography is normally noisy and low in contrast making detection of early signs of breast cancer (i.e. microcalcification and mass) difficult. Therefore, a lot of studies have been conducted to develop image processing techniques which would help in the detection of these early signs.